Evaluation of success and/or failure of endodontic treatment in non-vital teeth performed at the School of Dentistry at the Universidad del Valle. Case series - Ochoa, Luis; Moreno, Stevan; Piarpuzán, David; Rodríguez, Patricia; Herrera, Adriana; Moreno, Sandra (Revista Estomatología, 2014)
Introduction: The endodontic treatment in non-vital teeth is directed to the elimination of the infection through the biofilm removal biomechanics and remnants of necrotic tissue, in order to eliminate infection and generate periapical tissue repair. Objective: To determine the success or failure of endodontic treatment in non-vital teeth performed by dental students under supervision. Materials and methods: In this article 3 clinical cases of patients undergoing endodontic procedures with non-vital pulps track 4 and 6 years are presented. Results: Two of the 3 cases show a process of incomplete periapical tissue regeneration at the time of observation. The third case shows a process of subsequent periodontal disease to endodontics leading to tooth loss. Conclusions: Is necessary to conduct a study with a sample size calculated to determine what percentage of success and failure of endodontic treatment in non-vital teeth, performed by undergraduate dental students under supervision, and to determine those factors that directly influence both outcomes.